Economic origins of dictatorship and democracy - Acemoglu, Daron; Robinson, James A., 1960- (Cambridge ; New York : Cambridge University Press, 2006)
This book is the first to use modern social science methodology systematically to explain why some countries are democracies while others are not. Why does democracy sometimes persist and consolidate while other times it collapses? The treatment shows that whether or not a society becomes democratic depends on several factors.
Questions and answers -- Paths of political development -- Our argument -- What do we know about democracy? -- Modeling politics -- Democratic politics -- Nondemocratic politics -- The creation and consolidation of democracy -- Democratization -- Coups and consolidation -- Putting the models to work -- The role of the middle class -- Economic structure and democracy -- Globalization and democracy -- Conclusions and the future of democracy.
Includes bibliographical references (pages 381-399) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Democracy -- Economic aspects; Democratization; Equality; Political culture; Dictatorship; Comparative government; Démocratie -- Aspect économique.; Démocratisation.; Inégalité sociale; Culture politique; Dictature; Institutions politiques comparées.; dictatorships; comparative politics; POLITICAL SCIENCE -- Political Ideologies -- Democracy; Dictature; Démocratie.; Démocratisation.; Aspects économiques.; Comportement politique; Analyse comparative; Modèles économiques.; Comparative government; Democracy -- Economic aspects; Democratization; Dictatorship; Equality; Political culture; Demokratie; Entstehung; Diktatur; Wirtschaftssystem; Ökonomische Theorie der Demokratie; Ökonomische Theorie der Politik; Democracy; Economic conditions; Equality; Dictatorships; Comparative government; Economic models; International comparisons; Overseas item; Electronic book; Electronic books